2022
DOI: 10.32604/jrm.2022.018950
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Essential Oil Composition, Phenolic Compound and Biological Activities of Salvia microphylla and Teucrium polium (Lamiaceae)

Abstract: Salvia microphylla and Teucrium polium are medicinal and aromatic plants with ethnobotanical uses. The present study was conducted to investigate the chemical composition of Salvia microphylla and Teucrium polium essential oils, the secondary metabolites, and the biological activities of their infusion and methanolic (MeOH) extracts. Essential oils were extracted by hydrodistillation from shoots Salvia microphylla and Teucrium polium. Phenolic content, antioxidant and antimicrobial activities were determined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Nabavi and Di Lorenzo [21] The results showed that the antibacterial activity, expressed as an inhibition zone, ranged from 7 to 18 mm for the application of 30 µL, suggesting high antibacterial activity. The concentration of the active ingredient in the bark depends on the species of cinnamon, the environment, and the bark application pattern [22]. Cinnamaldehyde has been reported to inhibit Siamese fighting fish pathogens, including Vibrio cholerae, Vibrio parahaemolyticus [23], Aeromonas hydrophila [4,8,9,24,25], Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…Nabavi and Di Lorenzo [21] The results showed that the antibacterial activity, expressed as an inhibition zone, ranged from 7 to 18 mm for the application of 30 µL, suggesting high antibacterial activity. The concentration of the active ingredient in the bark depends on the species of cinnamon, the environment, and the bark application pattern [22]. Cinnamaldehyde has been reported to inhibit Siamese fighting fish pathogens, including Vibrio cholerae, Vibrio parahaemolyticus [23], Aeromonas hydrophila [4,8,9,24,25], Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…Teucrium polium L. -the leaves are used as a spice in fish processing. The essential oil contains about 45 compounds, the important components of which are βcadinene, β-citronellol, carvacrol and eugenol (Khadhri et al 2022). T. polium aqueous extract (TPAE) has an antiatherothrombotic effect (Mohd Nor et al 2019).…”
Section: Lamiaceae Familymentioning
confidence: 99%